Highest slope line: poetic-critical relations of walking (Palíndromo, 2020)
This article deals with walking / moving as a line and its power in activating the city context, both thought from the contemporary artistic phenomenon. Starting from a brief survey and historical outline of how the line has been discussed in art history until it comes to walking as a practical procedure and creative method, the article then discusses its object in the contextual relationship between art, individual and poetic-political presence in the city. To this end, the main artistic reference is the action “Se Hace Camino al Andar”, by the Spanish artist Esther Ferrer, in its performance near the Salvem El Cabanyal Platform, in the city of Valencia / Spain. To build its arguments, the article uses as theoretical contributions the writings of the movements of the 1960s / 70s, Situationism and Fluxus, as well as the studies on the city of Michel de Certeau and on Tim Ingold’s line and displacement.
Keywords: line; walking; city; poetic-critical action